The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/smll.202206211
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide‐Based Stimulus‐Responsive Nanomedicines for Combination Cancer Immunotherapy

Abstract: According to the World Health Organization, there were approximately 9.96 million deaths from cancer in 2020. Although researchers are actively searching for new treatments, the outcomes have been unsatisfactory, with limited improvement in the five-year survival rates. [2] Until now, immunotherapy has become one of the four pillars of clinical cancer treatment, along with surgery, chemotherapy, and radiotherapy. [3] It endows the body with the ability to eliminate tumors and prevent recurrence by stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 395 publications
(506 reference statements)
0
10
0
Order By: Relevance
“…72 In recent years, a number of LOX delivery applications have used a variety of MOF materials. 34,[73][74][75][76] Table 2 summarises the LOXbased organic-inorganic hybrid nanocomposites used for tumour therapy.…”
Section: Lox-based Organic-inorganic Hybrid Nanocarriers For Tumour T...mentioning
confidence: 99%
See 1 more Smart Citation
“…72 In recent years, a number of LOX delivery applications have used a variety of MOF materials. 34,[73][74][75][76] Table 2 summarises the LOXbased organic-inorganic hybrid nanocomposites used for tumour therapy.…”
Section: Lox-based Organic-inorganic Hybrid Nanocarriers For Tumour T...mentioning
confidence: 99%
“…90,91 Due to its unique properties, The synergistic effect of the two factors significantly enhanced the levels of M1 macrophages in TME, thereby enhancing macrophage-mediated cancer immunotherapy. 74 ZIF-67 has a unique photothermal property that facilitates the combination of nanoplatforms with PTT. However, the studies and applications of ZIF-67 in drug delivery have been less in-depth than the studies regarding ZIF-8.…”
Section: Zeolitic Imidazolate Framework (Zifs)mentioning
confidence: 99%
“…Thus far, researchers around the world have developed a large number of competitive low-dimensional vdW material photodetectors. [12][13][14][15][16][17] From the perspective of microscopic crystal structure, low-dimensional vdW materials can generally be classified into three categories, including 0D vdW materials, [18][19][20][21] 1D vdW materials, [22][23][24][25][26] and 2D vdW materials. [27][28][29][30][31][32][33][34][35] Compared to the 0D and 2D counterparts, 1D vdW materials commonly host unique chain-like lattice structures, and therefore these materials are inclined to spontaneously form nanorod/nanowire/nanobelt/nanotube-like crystal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various types of nanoparticle-based delivery systems for controlled and sustained drug release, the transportation of insoluble drugs, and targeted therapy have been reported for the treatment of human diseases, including liver diseases. , However, their controlled release properties and targeting efficiency are unsatisfactory in complicated biological environments, partly due to their inherent immunogenicity, poor stability and dispersion, and rapid clearance in vivo . Therefore, enhancing the specificity and prolonging the circulation time of drugs and reducing their aggregation at nontarget sites are highly important for the clinical translation of nanopreparations. In recent years, the development of cell membrane-coated nanoparticles for high-efficiency and low-toxicity treatment has achieved great success. , Notably, it has been reported that nanoparticles coated with erythrocyte membranes, which contain membrane protein complexes that are crucial for immune tolerance, can prolong the circulation time of nanomaterials in blood and thus improve their therapeutic effects .…”
mentioning
confidence: 99%